Cinemato[graphos] : as ocorrências da palavra no cinema das vanguardas [anos 1920] - Guilherme Guazzi Rodrigues (2008)
Analysis of the main occurrences of the word [graphos] as a rhetoric element in the process of constructing the image and the production of meaning in the German, French and Russian avant-garde [dec. 1920]. A pseudo-taxonomic study of the main applications of the written word in the cinema as functional or poetic elements, the classifications and their variants. Survey of occurrences of the word-image in the visual arts and poetry in the passage from 19th to 20th century in order to identify possible conceptual and formal influences to which cinematographic production was submitted. The reflection considers about the behavior of writing and reading acts, when the word and/or its graphic morphology is submitted to the action of several space-temporal aspects, checking if the dynamic aspect implicit into this media requires some other organization way, some other syntax which sets up to words connections other than those from its symbolic aspect. Here we have a discussion about the kinematics medias ability to enhance the basic ambiguity implicit on the graphic record of the word, that is, its symbolic function associated with its iconic function, as well as enlarging the semantic field of the word.